Non-exhaustive test for aerobic capacity determination in running rats - Manchado-Gobatto, F. B.; Gobatto, C. A.; Contarteze, R. V. L. [UNESP]; Mello, M. A. R. [UNESP] (Natl Inst Science Communication-niscair, 2011)
A simple and applicable method for non-exhaustive aerobic evaluation in running rats is described. Wistar rats were submitted to running test at different velocities (10, 15, 20, 25 m/min) with 48 h recovery among them. At each velocity, the rats ran two bouts of 5 min with 2 min of rest between bouts. Blood samples were collected at the end of each bout for lactate determination. For each intensity, delta lactate was calculated and using deltas obtained by four tests, an individual linear interpolation was plotted. The y-intercept of linear interpolation was the null delta lactate equivalent to the critical velocity (CV). To verify the lactate stabilization at CV, the animals were submitted to 25 min of continuous exercise (15, 20, 25 m/min), with blood collection every 5 min. The estimated CV was 16.6 +/- 0.7 m/min, with significant linear regressions (R=0.90 +/- 0.03). The rats presented maximal lactate steady state (MLSS) at 3.9 +/- 0.4 mmol/L, at 20 m/min. The CV was less than MLSS but significantly correlated with this parameter (r=0.78). This non-exhaustive test seems to be valid for the aerobic evaluation of sedentary rats and this protocol underestimates the MLSS in 20%. This test seems to be the interesting method for the evaluation of rats submitted to acute exercise or physical training.
Keywords: Blood lactate; Critical load; Double bouts exercise test; Maximal lactate steady state; Running